2019
DOI: 10.1111/cxo.12865
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central corneal thickness measurements with standard ultrasonic pachymetry and optical devices

Abstract: Background: To compare the repeatability and agreements of central corneal thickness measurements of healthy individuals obtained by Scheimpflug-Placido topographer (Sirius), anterior segment spectral domain optical coherence tomography (Spectralis) (AS-OCT), optical biometry (AL-Scan) and ultrasonic pachymetry. Methods: Sixty-four eyes of 32 subjects with no ocular or systemic diseases were included in this study. Central corneal thickness measurements performed with Sirius, AS-OCT, optical biometry AL-Scan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
(18 reference statements)
2
14
0
Order By: Relevance
“…Although there are no data in the literature on the reliability of these methods in patients that have undergone CXL, they have been reported to measure CCT with high reliability in healthy individuals. 11,24 Although there was a correlation between the devices in terms of pachymetry measurements, AS-OCT measured CCT as approximately 23.97 μm thicker than topography, and MCT as 16.21 μm thicker than topography. The Bland Altman analysis also revealed that LoA were 91.5 μm for CCT and 67.8 μm for MCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no data in the literature on the reliability of these methods in patients that have undergone CXL, they have been reported to measure CCT with high reliability in healthy individuals. 11,24 Although there was a correlation between the devices in terms of pachymetry measurements, AS-OCT measured CCT as approximately 23.97 μm thicker than topography, and MCT as 16.21 μm thicker than topography. The Bland Altman analysis also revealed that LoA were 91.5 μm for CCT and 67.8 μm for MCT.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that different devices can measure pachymetry differently because they use different technological imaging principles. 24 It has also been considered that the tear film layer may be effective in the pachymetry differences between Scheimpflug imaging and AS-OCT techniques. 25 These mechanisms can also explain the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The strain on the corneal endothelium by a variety of mechanical and toxic influences which occur during cataract surgery is one of the greatest risk factors for postoperative complications [3,[26][27][28][29] . Compromising of the corneal endothelium leads to a transitory reduction of its capability to dehydrate the corneal stroma, thus leading to a corneal edema.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations have been performed between different imaging techniques. Different authors have compared results of Scheimpflug imaging and anterior segment-OCT [12,21,29,[38][39] . Most authors emphasize low comparability between different techniques whereas validity within every single technique is very high.…”
Section: Discussionmentioning
confidence: 99%
“…Maresca et al [7] Scheimpflug camera and USP Significant High correlation Not interchangeable Scotto et al [8] OCT, non-contact specular Significant Poor repeatability Not interchangeable microscopy, and UPS Binnawi et al [10] OCT, pachymetry, and Significant High correlation Not interchangeable TMS-5 topography Dogan et al [11] Scheimpflug-Placido Significant High repeatability Not interchangeable topography, OCT, optical biometry, and USP González-Pérez et al [12] USP, non-contact Significant High repeatability Interchangeable except tono/pachymetry, Pentacam except tono-pachymetry tono/pachymetry corneal topography, and OCT Gokcinar et al [13] OCT, corneal topography, Significant -Not interchangeable optical biometry, specular microscopy, and USP Teberik et al [14] Pentacam HR, Sirius -High consistency Interchangeable topography, iPac, and Echoscan US-500 Mansoori et al [15] OCT, optical biometry, and Significant -A high level of agreement Sirius anterior segment analysis between optical biometry and Sirius topography, but not OCT Kiraly et al [16] IOL Master 700, Pentacam HR, Significant Not interchangeable and Cirrus HD-OCT Ozyol and Ozyol [17] SD-OCT with Scheimpflug Non-significant -Interchangeable system, optical biometry, and non-contact pachymetry Erdur et al [18] Ultrasonic pachymetry, SD-OCT, and Non-significant Strong correlation Interchangeable non-contact specular microscopy Calvo-Sanz et al [19] OCT, non-contact specular Significant -OCT and USP offered highly microscopy, and USP comparable results, but not non-contact specular microscopy Bayhan et al [20] SD-OCT, Sirius Scheimpflug-Placido topographer, Lenstar optical low-coherence reflectometry, and USP Non-significant Correlated closely Interchangeable HD-OCT: High-definition optical coherence tomography; OCT: Optical coherence tomography; SD-OCT: Spectral domain optical coherence tomography; USP: Ultrasound pachymetry. 10) compared the CCT measurements of OCT, pachymetry, and Scheimpflug-Placido topography using the TMS-5 device (Tomey GmbH, Nürnberg, Germany) in 122 eyes and reported a statistically significant difference in the mean CCT value between the methods, although there was a significant and strong correlation between them.…”
Section: Difference Correlation or Repeatability Conclusionmentioning
confidence: 99%